Описание самца бобрового клеща Федюшина—Xenocastor fedjushini A.Z., 1941 (Acariformes, Glycyphagidae) - Щур, Л.Е. (Вестник зоологии, 1976)
A description and drawings of the male of Xenocastor fedjushini A.Z., 1941 are presented.